Transient global amnesia in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts, and leukoencephalopathy (CADASIL) - Yu. М. Kyrianov; N. А. Totolyan (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Transient global amnesia (TGA) is characterized by a sudden onset of total memory dysfunction, and loss of the ability to memorize information, followed by anterograde, and sometimes, retrograde amnesia, and reproduction of current events with patient’s consciousness alert, accompanied by one’s repetitive questioning during this very episode that lasts less than 24 hours (usually 1-8 hours). The process involves mesial temporal lobes and hippocampi. Pathogenesis of TGA includes venous congestion with Valsalva-like activities, other vascular dysfunction, and migraine. The article contains literature review on the development of TGA in patients with Multiple Sclerosis and Cerebral Autosomal Dominant Arteriopathy and Subcortical Infarcts and Leukoencephalopathy (CADASIL), which is not common for such patients, and describes a rare clinical case of confirmed CADASIL, in whom first acute vascular ischemic attack presented by TGA developed. In this patient, CADASIL was diagnosed earlier, and was based on the presence of migraine in anamnesis, common for CADASIL patients MRI abnormalities, and the result of molecular-genetic analysis, which showed gene NOTCH3 heterozygous mutation: р.207 R>R/C. Neurological examination revealed no focal neurological signs. Brain MRI in diffusion option (DWI) revealed a small pinpoint ischemic focus in left hyppocampus, which is characteristic for TGA. Despite of frequent review of migraine and subcortical ischemic events in these patients, the history of TGA is solely reported in literature. Reports of TGA development in patients with multiple sclerosis are also sole.